Analisis Perbandingan Sistem Hukum Eropa Kontinental dengan Sistem Anglo Saxon yang Ditinjau dari Perspektif Sistem Juri - Achmad Barlian Dipantara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Continental European legal system and the Anglo-Saxon legal system, particularly in the context of jury application, by exploring the philosophical, procedural, and normative implications of each system. The Continental European legal system, rooted in the civil law tradition, emphasizes the codification of laws as the primary source of legal rules, often sidelining the role of juries in the judicial process. On the other hand, the Anglo-Saxon legal system, which adheres to common law, places the role of the jury as a crucial element in determining facts and delivering verdicts in trials. This research utilizes a comparative approach to identify fundamental differences between the two systems, with an emphasis on the role and authority of juries in the context of law enforcement and judicial processes. This analysis includes a study of the role of juries in each legal system, their impact on procedural justice, as well as the shortcomings and advantages that arise from the implementation of both systems in the context of community life. Using a normative qualitative research method, this study concludes that although there are significant differences in the application of the jury system, both systems contribute importantly to the development of justice principles within the broader framework of international justice. This research also presents recommendations regarding the potential integration of positive elements from each system to enrich legal practices in Indonesia.